The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1093/infdis/jiw081
|View full text |Cite
|
Sign up to set email alerts
|

Climatic Drivers of DiarrheagenicEscherichia coliIncidence: A Systematic Review and Meta-analysis

Abstract: These results suggest that increases in ambient temperature correspond to an elevated incidence of diarrheagenic E. coli and underscore the need to redouble efforts to prevent the transmission of these pathogens in the face of increasing global temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 42 publications
6
49
0
1
Order By: Relevance
“…Several bacterial pathogens were more prevalent during hot and rainy weather, which could favor the growth of bacteria in the environment or the contamination of water sources [29]. We found ST-ETEC was generally associated with warmer weather (in Mozambique, Pakistan, India, and Bangladesh), consistent with the previously observed association between ETEC and higher temperatures and not rainfall [30, 31]. A significant association between Cryptosporidium and rainy weather was identified in The Gambia, Mali, and Mozambique.…”
Section: Discussionsupporting
confidence: 88%
“…Several bacterial pathogens were more prevalent during hot and rainy weather, which could favor the growth of bacteria in the environment or the contamination of water sources [29]. We found ST-ETEC was generally associated with warmer weather (in Mozambique, Pakistan, India, and Bangladesh), consistent with the previously observed association between ETEC and higher temperatures and not rainfall [30, 31]. A significant association between Cryptosporidium and rainy weather was identified in The Gambia, Mali, and Mozambique.…”
Section: Discussionsupporting
confidence: 88%
“…WHO (42) estimates that climate change will cause an additional 48,000 diarrheal deaths in 2030. A systematic review and meta-analysis by Philipsborn et al (43) found that an increase of 1 • C in mean monthly temperature was associated with an 8% increase in incidence of diarrheagenic Escherichia coli (E. coli ).…”
Section: Climate Change and Wash-related Diseasementioning
confidence: 99%
“…There are several interventional factors that may influence the pathogen transmission such as sanitation infrastructure, drinking water distribution systems, food handling practices, nutritional habits of societies, etc. (Auld et al, 2004;Newman et al, 2015;Philipsborn et al, 2016;Tarique et al, 2007;Van de Venter, 2000). The earth weather variations may influence the human activities such as seasonal business, immigration, winter-summer habitude, and corporeal exercises that play important roles in human capacities and responses.…”
Section: Discussionmentioning
confidence: 99%